Genotyping of Brazilian Giardia duodenalis human axenic isolates - Coradi, S. T.; David, E. B. [UNESP]; Oliveira-Sequeira, T. C. G. [UNESP]; Ribolla, P. E. M. [UNESP]; Carvalho, T. B. [UNESP]; Guimaraes, S. [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2011)
Giardia duodenalis is a complex species that comprises at least seven distinct genetic groups (A to G), but only genotypes A and B are known to infect humans and a wide variety of other mammals. Regardless of biological, biochemical and antigenic analysis, several isolates maintained in vitro were not genetically typed yet. So, in the present study, five Brazilian axenic isolates obtained from asymptomatic and symptomatic patients were typed in order to determine the major genetic groups to which the isolates belonged. DNA was extracted from axenic trophozoites, fragments of glutamate dehydrogenase (gdh) and triosephosphate isomerase (tpi) genes were amplified by PCR and the isolate genotyping was carried out using restriction fragment length polymorphism (RFLP) and DNA sequencing for both genes. The results revealed that all isolates were assigned to genotype A at both analyzed loci. Indeed, DNA sequence analysis classified the four isolates obtained from asymptomatic individuals into subtype AII, while the isolate obtained from the symptomatic patient was typed as subtype AI. Despite of the limited number of isolates assessed, the findings presented herein provide interesting insights on the occurrence of Giardia genotypes in Brazil and hold the perspective for future molecular and epidemiological investigations.
Keywords: Giardia duodenalis; axenic isolates; molecular typing; genotype